River and coast geo facts - Howell, Izzi (Geofacts (Crabtree Publishing Company), 2018)
Examines the geographical science behind rivers and coasts, highlighting their structure, types, erosion and change, and flooding. Focuses on six specific rivers and coasts. Includes a glossary, text-related questions with an answer key, resources for further information, diagrams, maps, and color photographs.